Pengaruh Social Responsibility, Corporate Governance dan Tri Hita Karana Terhadap Kinerja Keuangan - Ni Wayan Supartini; I Putu Deddy Samtika Putra (UNHI Press, 2022)
The purpose of this study was to determine the effect of the application of corporate social responsibility, good corporate governance and tri hita karana on the financial performance of LPD in Ubud Regency, Gianyar Distric. This research was conducted in all LPD in Ubud regency. The number of samples used is 32 LPD, with porpusive random sampling. Data collection is done through questionnaires. The analysis technique used is multiple linear regression. The results of hypothesis testing indicate that corporate social responsibility have a positive effect on the financial performance of LPD in Ubud regency, good corporate governance have a positive effect on the financial performance of LPD in Ubud regency and the tri hita karana have a positive effect on the financial performance of LPD in Ubud regency.